Knowledge and perception on type2 diabetes and hypertension among HIV clients utilizing care and treatment services: a cross sectional study from Mbeya and Dar es Salaam regions in Tanzania - Gibson B. Kagaruki; Mary T. Mayige; Esther S. Ngadaya; Andrew M. Kilale; Amos Kahwa; Amani F. Shao; Godfather D. Kimaro; Chacha M. Manga; Doris Mbata; Godlisten S. Materu; Ray M. Masumo; Sayoki G. Mfinanga (BMC, 2018)
Abstract Background Type2 Diabetes and Hypertension (T2DM/HTN) have become serious threats to the health and socio-economic development in the developing countries. People living with HIV (PLHIV) infection are more vulnerable of developing T2DM/HTN due to HIV infection itself and antiretroviral treatments. The situation is worse when behavioral and biological risk factors are pervasive to PLHIV. Despite this vicious circle; information on the level of knowledge and perception regarding prevention of T2DM/HTN, risks factors and associated complications among PLHIV is not well documented in Tanzania. The aim of this paper was assess the level of T2DM/HTN knowledge and perception among PLHIV and utilizing care and treatment clinic (CTC) services. Methods A cross-sectional study was conducted in randomly selected 12 CTCs between October 2011 and February 2012. Data on demographic characteristics, type 2 diabetes and hypertension knowledge and perception were collected from the study participants. Results Out of 754 PLHIV and receiving HIV services at the selected CTCs, 671 (89%) consented for the study. Overall 276/671(41.1%) respondents had low knowledge on type2 diabetes and hypertension risk factors and their associated complications. Locality (rural) (AOR = 2.2; 95%CI 1.4-3.4) and never/not recalling if ever measured blood glucose in life (AOR = 2.3; 95%CI 1.1-5.7) were significant determinants of low knowledge among clients on ART. Being currently not having HIV and T2DM/HTN co-morbidities (AOR = 2.2; 95%CI 1.2-4.9) was the only determinant of low knowledge among ART Naïve clients. With regard to perception, 293/671(43.7%) respondents had negative perception on diabetes and hypertension prevention. Sex (female) (AOR = 2.0, 95%CI 1.2-2.9), being aged < 40 years (AOR = 1.6; 95%CI 1.1-2.5) and education (primary/no formal education) (AOR = 4.4; 95%CI 2.0-9.8) were determinants for negative perception among clients on ART while for ART Naïve clients; HIV and T2DM/HTN co-morbidities (AOR = 2.0; 95%CI 1.2-4.6) was the main determinant for negative perception. Conclusion Considerable number of respondents had low level of knowledge (41.1%) regarding T2DM/HTN specifically on the risk factors, prevention strategies and their associated complications and negative perception (43.7%) towards healthy practices for mitigating risk behaviors of the diseases. There is need for promoting awareness of T2DM/HTN risk factors and complications by considering determinants of low knowledge and negative perception among PLHIV.